A case of simvastatin‐induced myopathy with SLCO1B1 genetic predisposition and co‐ingestion of linagliptin and Stevia rebaudiana. (3rd February 2019) - Chan, Jones Chun Man; Ng, Ming‐Him; Wong, Raymond Siu Ming; Tomlinson, Brian
Summary: What is known and objective: SLCO1B1 T521>C variant carriers are susceptible to simvastatin‐induced myopathy. We report a patient who developed rhabdomyolysis possibly triggered by a drug–drug and/or herb–drug interaction. Case description: A 69‐year‐old man presented with myalgia and weakness progressing to severe rhabdomyolysis. He had been taking 40 mg simvastatin daily for 10 years and recently consumed supplements, including Stevia rebaudiana and linagliptin. Genotyping revealed he carried one copy of SLCO1B1 T521>C and two copies of ABCG2 C421>A. What is new and conclusion: Despite apparent long‐term safe administration, co‐ingestion of simvastatin and other CYP3A4 inhibitors may result in severe myopathy in those at increased genetic risk.